2022
DOI: 10.1038/s41420-022-01093-3
|View full text |Cite
|
Sign up to set email alerts
|

Effective tumor cell abrogation via Venetoclax-mediated BCL-2 inhibition in KMT2A-rearranged acute B-lymphoblastic leukemia

Abstract: Dysregulation of the intrinsic BCL-2 pathway-mediated apoptosis cascade is a common feature of hematological malignancies including acute B-lymphoblastic leukemia (B-ALL). The KMT2A-rearranged high-risk cytogenetic subtype is characterized by high expression of antiapoptotic protein BCL-2, likely due to the direct activating binding of KMT2A fusion proteins to the BCL2 gene. The BCL-2 inhibitor venetoclax (VEN) has proven great clinical value in other blood cancers, however, data on B-ALL is sparse and past st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Previous studies by others and our group have shown that prolonged VEN incubation induces BCL-2, MCL-1, and BCL-xL anti-apoptotic protein expression [ 3 , 22 ]. Combination approaches should therefore counteract these mechanisms to synergistically tip the balance toward apoptosis induction [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies by others and our group have shown that prolonged VEN incubation induces BCL-2, MCL-1, and BCL-xL anti-apoptotic protein expression [ 3 , 22 ]. Combination approaches should therefore counteract these mechanisms to synergistically tip the balance toward apoptosis induction [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The human B-ALL cell lines SEM and RS4;11 were obtained from DSMZ (Braunschweig, Germany) and cultivated as previously described [ 3 ]. A control for authenticity (cell surface flow cytometry) and mycoplasma contamination was performed at regular intervals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations